Interaction of Labour Market and Education System in Germany - Knodel, Ludmila (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
The article deals with the problems of interaction between labour market and education system in Germany. In Germany, there is a very original model of the interaction of the labour market and the education system. In Germany there are several ways to solve this problem. A significant difference between the German systems of vocational training is the concentration and integration of educational resources, high organization and the discipline of educational process. Labour migration is strongly encouraged, because in such a simple way to solve the problem of the state of post-war shortage of personnel. A large number of foreign workers increased competition in the labor market. In the last decade in Germany kept fairly high level of unemployment, which, according to official data, more than 10% today. in Germany the unemployment rate for specialists with higher education is only 3. 5%. In general, in Germany there are nearly four million unemployed, equal to 10% of the working population. Germany desperately short of engineers and computer geeks. Now the scarce specialties were added and teachers and doctors. In such circumstances, the problem of vocational education in Germany is social. In Germany, there are several ways to solve this problem. Education in Germany is the world’s classic study. The education system in Germany was an example building training for the world. Today, higher education in Germany, like other European countries in crisis. German universities are among the national leaders in research.